ANALISIS DAERAH RAWAN BANJIR DAN TANAH LONGSOR DI DAERAH ALIRAN SUNGAI LAHUMBUTI HULU PROVINSI SULAWESI TENGGARA - La Baco; Sitti Marwah; kahirun kahirun; Umar Ode Hasani (Jurnal Ecogreen, 2019)
ABSTRACTFloods and landslides are a form of natural disaster that causes harm to humans. Floods and landslides are caused by many factors which are broadly distinguished by natural factors and human factors. The purpose of this study was to analyze flood susceptible areas and landslide susceptible areas in the Upper Lahumbuti watershed. This research was conducted in the Upper Lahumbuti watershed using the survey method. The results showed that the level of flood vulnerability in the Upper Lahumbuti watershed included a medium vulnerability level of 15,022.58 ha (65.22%), an area that was not susceptible to flooding reaching an area of 5,004.29 ha (21.73%), and an area of flood susceptible reaches 3,005.23 ha (13.05%). Areas susceptible to landslides in the Upper Lahumbuti watershed reached an area of 17,599.08 ha (76.41%), the area included in the rather landslide susceptible category was 2,997.19 ha (13.01%), while the area with medium vulnerable categories was 2,159.13 (9.37%). Keywords: flood, landslide, flood susceptible areas, landslide susceptible areas, Upper Lahumbuti watershed ABSTRAKBanjir dan tanah longsor merupakan bentuk bencana alam yang menyebabkan kerugian bagi manusia.  Banjir dan tanah longsor disebabkan oleh banyak faktor yang secara garis besar dibedakan atas faktor alam dan faktor manusia.  Tujuan penelitian ini adalah untuk  menganalisis daerah rawan banjir dan daerah rawan longsor di Daerah Aliran Sungai Lahumbuti Hulu. Penelitian ini dilakukan di DAS Lahumbuti Hulu dengan menggunakan metode survei. Hasil penelitian menunjukkan bahwa tingkat kerawanan banjir di DAS Lahumbuti Hulu meliputi tingkat kerawanan sedang dengan luas 15.022,58 ha (65,22 %),  daerah yang tidak rawan banjir mencapai luas 5.004,29 ha (21,73 %), dan luas wilayah yang rawan banjir mencapai 3.005,23 ha (13,05 %). Daerah rawan longsor di DAS Lahumbuti Hulu mencapai luas 17.599,08 ha (76,41 %), wilayah yang termasuk kategori agak rawan longsor adalah 2.997,19 ha (13,01 %), sementara itu luas wilayah dengan kategori rawan sedang adalah seluas 2.159,13 (9,37 %). Kata Kunci: banjir, tanah longsor, daerah rawan banjir, daerah rawan longsor, DAS Lahumbuti Hulu